Model Pendidikan Karakter Berbasis Tradisi Katoba dalam Budaya Masyarakat Muna di Sulawesi Tenggara - Hasriany Amin (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2013)
ABSTRACT The objective of this study is to discover a model-based educational character of Katoba tradition that can be a specific methodologies to inculcate the values of local wisdom in the community and be a solution to the moral problem. This study is important because today's emerging phenomenon of attitudes and behaviors that are less noble character among students, teenagers, and young people, while character education in schools has not been going well. The research method applied is descriptive qualitative, selecting informants by purposive sampling. The results shows that: First, the Muna Kendari city have educational character model that is based on local wisdom of Katoba tradition. Second, the model-based educational character Katoba aims to introduce religious values in early children aged of 7-12 years, ahklak teachings instilled in children by introducing the basic things that contains the value of the good and evil in the Muna language nimotehi be nimokodo (case that are forbidden and don'ts), to teach children to appreciate the values of social life, and avoid the things that are not his (hakunasi). Kata Kunci: model, educational character, katoba, Muna